Answer:
D. 40x - 8
C. (5x-1)(-2+7+3)
----------------------------------------------
-2(5x - 1) + 7(5x - 1) - 3(-5x + 1)
= -10x + 2 + 35x - 7 +15x - 3
= -10x - 35x +15x + 2 - 7 - 3
= 40x - 8
D. is correct.
----------------------------------------------
(5x-1)(-2 + 7 + 3)
= -10x + 2 + 35x - 7 +15x - 3
= 10x - 35x +15x + 2 - 7 - 3
= 40x -8
which is as same as the answer choice D. and the answer you get from solving the -2(5x - 1) + 7(5x - 1) - 3(-5x + 1), so
C. is correct, too
-------------------------------------------------
There seems to be a typo in answer choice A. so I cannot determine if A is also correct or not...